Daniel Everett. Why There Are No Clitics. An Alternative Perspective on Pronominal Allomorphy. Texas: Summer lnstitute of Linguistics and The University of Texas. 1996. 188 pp. - García Granados, Jorge (Lexis, 1998)
No contiene resumen